Analisis Peran Kompensasi Kerja Dan Pelatihan Kerja Terhadap Kinerja Karyawan Foodpedia Group - Teguh Setiawan Wibowo; Hendy Tannady; Dila Erlianti; Rudi Setiadi; Suparman Suparman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of job training and job compensation on the performance of FoodpediaGroup Jakarta employees. The population in this study were all employees of the Foodpedia Group Jakarta outlet asmany as 100 employees with the measuring instrument used was a questionnaire distributed via google form. Theresearch method used is a quantitative method where data collection is carried out by multiple linear regression analysisand uses the F test and T test. The results of the hypothesis in this study are; that job training has a significant effecton employee performance, that work compensation has a significant effect on employee performance, while the resultsof the f test of both variables have a simultaneous effect. Keywords: Job Training, Job Compensation, Job Performance